Design of PI Controller using Optimization Method in Fractional Order Control Systems. Issue 4 (2018) - Dogruer, Tufan; Tan, Nusret
Abstract: In control systems, controller preference and design is an important issue for meeting the desired design criteria. In this paper, PI controller design was performed by using optimization method for fractional order systems. First, all the PI controller parameters that make the control system stable are calculated by using the stability boundary locus method. However, each controller parameter selected in the stability region may not be able to optimally control the system. Optimal controller parameters that provide the best control from the PI controller parameters that make the system stable by using the optimization method are obtained. In the optimization process, the optimal PI controller parameters are calculated by using the integral performance criterion based on the error. Simulation studies have been done for closed loop control system including a fractional order transfer function with time delay. It has been shown that the presented method can be successfully applied to fractional order control systems.